2015
DOI: 10.1108/sajgbr-07-2014-0052
|View full text |Cite
|
Sign up to set email alerts
|

A grounded theory study on family-to-work enrichment

Abstract: Purpose – The purpose of this paper is to demonstrate systematic application of grounded theory to understand antecedents, moderators and consequences of family-to-work enrichment in India. The paper throws light on the key tenets of grounded theory research and explains its use as a rigorous method for management research. Design/methodology/approach – “Paradigm model” of grounded theory was used for data analysis. Data were collected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…This contribution is important as it points to the circumstances in which high self-efficacy can facilitate behaviours, valuable for the organisation. Moreover, it extends to prior work on family-work enrichment, an area considered to be relatively understudied (Mishra, 2015;Jain & Nair, 2017), and shows organisations and employees that non-work roles play a role in service delivery OCB. Third, we will complement the relatively scant literature on service-oriented OCB.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…This contribution is important as it points to the circumstances in which high self-efficacy can facilitate behaviours, valuable for the organisation. Moreover, it extends to prior work on family-work enrichment, an area considered to be relatively understudied (Mishra, 2015;Jain & Nair, 2017), and shows organisations and employees that non-work roles play a role in service delivery OCB. Third, we will complement the relatively scant literature on service-oriented OCB.…”
Section: Introductionsupporting
confidence: 53%
“…Therefore, organisations should encourage employees to schedule activities on time (e.g. use time management tools), protect family and work times and inform family members of the scheduled activities in order for them to be mentally prepared (Mishra, 2015). Another way to facilitate family-work enrichment is for organisations to establish ties with their employees' family members by inviting them to participate in celebratory events (Jain & Nair, 2017).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The of the explored women reported different experiences of enrichment due to differences in familial contextual conditions. Similarly, Mishra (2015) demonstrated that individuals' experience of family support can change with the size of the family. This is because individuals who live in large and extended families receive some additional support benefits than those living in small families.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that support and environmental networks can mediate and influence the WFE experience. Accordingly, Mishra (2015) found that the resources in the community can improve the link between family support resources and family-to-work achievement in two ways. First, the resources available in the community, such as close neighbors, access to kindergartens with desirable facilities, services offered by cleaning companies, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation